Investigating the Effects of COVID-19 on the World Trend of Childhood Vaccination: A Systematic Review - Pouran Varvani Farahani; Candan Öztürk (Mazandaran University of Medical Sciences, 2024)
Background and Objectives: The global COVID-19 pandemic has significantly impeded children's vaccination programs, endangering the public's health. Concerns have risen about the impact on vaccination coverage rates and the need for effective strategies to overcome such obstacles. Accordingly, this study investigates the effects of COVID-19 on the worldwide trend of childhood immunization. Methods: The Web of Science database was comprehensively searched from January 2020 to July 2023. The English keywords were TS=(["SARS-CoV-2" OR "COVID-19" OR "coronavirus") AND ("pediatric immunization" OR "childhood vaccination" OR "vaccine coverage"]). The two authors of this research independently assessed each study that satisfied the inclusion criteria. The preferred reporting items for systematic reviews and meta-analyses checklist guided the systematic review process, and VOSviewer software was used for bibliometric analysis.  Results: The initial search yielded 624 articles, leaving 62 articles for analysis. The most frequent keyword searches were COVID-19 (n=37, total link strength=78). The US was the most productive country in terms of articles (n=19, citations=411). Furthermore, visualization mapping showed that "the journal of vaccine" was the top source with a total link strength of 1560 and citations of 139. The disruptions were multifaceted and resulted from various factors, such as changes in vaccination coverage rates, vaccine hesitancy, missed or delayed vaccinations, catch-up immunization efforts, and disruptions to routine immunization programs. Declines in vaccination coverage were observed for various vaccines, including measles, polio, and diphtheria-tetanus-pertussis. Conclusions: The results showed the critical need for action to minimize the COVID-19 pandemic's negative effects on childhood immunization. Policymakers and healthcare providers should prioritize restoring and strengthening immunization services, addressing vaccine hesitancy, and implementing catch-up vaccination programs.